Tocilizumab in patients with multisystem Erdheim–Chester disease. (3rd June 2017) - Berti, Alvise; Cavalli, Giulio; Guglielmi, Barbara; Biavasco, Riccardo; Campochiaro, Corrado; Tomelleri, Alessandro; Nicoletti, Roberto; Panzacchi, Andrea; Ferrarini, Marina; Dagna, Lorenzo
ABSTRACT: Treatment of Erdheim–Chester disease (ECD), a rare non-Langerhans histiocytosis, relies on interferon-α, chemotherapeutic agents such as purine analogs, cytokine-blocking agents and BRAF inhibitors. Since interleukin (IL)-6 levels are elevated in serum and lesions of ECD patients, we evaluated the therapeutic efficacy and safety of IL-6 blockade with tocilizumab. We conducted an open-label, single-arm, phase II, prospective study of tocilizumab in three patients with multisystem ECD and poor tolerance/contraindications to IFN-α. Modifications of symptoms attributed to ECD represented the criteria for evaluation of clinical response. Changes at positron emission tomography scan, computed tomography scan, and magnetic resonance imaging at month 6 represented the main criteria for the evaluation of radiological response. Sustained complete clinical response and partial radiological improvement were observed in two patients, paralleled by modulation of systemic pro-inflammatory mediators. In spite of disease stabilization or improvement at extra-neurological sites, a third patient experienced a radiologic and clinical progression of central nervous system involvement, mirrored by a dramatic increase of circulating IL-6 and related cytokines. These findings indicate that IL-6 inhibition can be effective in ECD, but caution is advisable in patients with neurologic involvement. IL-6 emerges as a central mediator in ECD pathogenesis.